Study of ZnO Thin Films Prepared by Chemical Bath Deposition - Azimul Haque, Md; Mahalakshmi*, S. (Asian Journal of Chemistry, 2013)
Zinc oxide thin films were deposited on glass substrates by chemical bath deposition. Thin films were prepared from a solution of zinc acetate, triethanolamine and sodium hydroxide with different stirring times for zinc acetate and triethanolamine. The stirring times were 1, 2 and 3 h. The deposition temperature was 80 ºC. The deposited films were annealed at 200 ºC for 1 h. The effect of stirring time on structural properties of the film as well as composition, surface morphology was studied. ZnO thin films are widely used for optoelectronic and sensor applications.